Paul Harro-Harring: visualidade melancólica da escravidão no Rio de Janeiro - 1840 - Macedo, Rafael Gonzaga de (2014)
This dissertation had as its aim to build a visual history from the images produced by the Teutonic Danish traveler Paul Harro-Harring, who came to Brazil in 1840. Through a series of drawings and watercolor paintings, this traveler and artist portrayed landscapes and scenes from slave-related daily life in Rio de Janeiro. Our research treated such images as a visual source to a certain manner of producing and assigning meaning to the world, building our interpretation and interaction with its images in the core of a historiography tradition named Visual Studies. Visual Studies carry in their theoric outline the term visuality , which refers to the way a certain look will perceive and attribute meaning to the visible. Thus, the Visual Studies address on culture and the visual dimension in every kind of cultural production in a determined historical-cultural context. From these references, it was aimed to establish a relation between the landscape and nature conceptions in the romantic painting with the Rio de Janeiro‟s scenery created by the artist. There was a description and interpretation of images that pictured slave trade scenes and the cultural relationships between the slaves among themselves and with their landlords. To do such a study, it was considered not only the imaginary and the cultural background of the artist, but also the tension of the experience lived by him in 1840‟s Rio de Janeiro. It is concluded that his perception of the world, his political and philosophical conceptions on culture notions, nation and men and also the concrete conditions of the slaves‟ existence feeded his perception and constellated the visuality present in his images